Beauty Hunkering Memory - Kilates, Marne (Likhaan: The Journal of Contemporary Philippine Literature; Vol 2 (2008): Likhaan 2, 2010)
At the Carenderia Tampuhan Hidalgo's Vendadora Recollections of Paradise The Huntress by Bencab Delotavo's Diaspora Junkscape